Characterization of a novel cold-adapted intracellular serine protease from the extremophile Planococcus halocryophilus Or1 - Rasmussen, Casper Bøjer; Scavenius, Carsten; Thøgersen, Ida B.; Harwood, Seandean Lykke; Larsen, Øivind; Bjerga, Gro Elin Kjaereng; Stougaard, Peter; Enghild, Jan J.; Thøgersen, Mariane Schmidt (Frontiers in Microbiology, 2023)
The enzymes of microorganisms that live in cold environments must be able to function at ambient temperatures. Cold-adapted enzymes generally have less ordered structures that convey a higher catalytic rate, but at the cost of lower thermodynamic stability. In this study, we characterized P355, a novel intracellular subtilisin protease (ISP) derived from the genome of Planococcus halocryophilus Or1, which is a bacterium metabolically active down to -25°C. P355’s stability and activity at varying pH values, temperatures, and salt concentrations, as well as its temperature-dependent kinetics, were determined and compared to an uncharacterized thermophilic ISP (T0099), a previously characterized ISP (T0034), and Subtilisin Carlsberg (SC). The results showed that P355 was the most heat-labile of these enzymes, closely followed by T0034. P355 and T0034 exhibited catalytic constants (kcat) that were much higher than those of T0099 and SC. Thus, both P355 and T0034 demonstrate the characteristics of the stability-activity trade-off that has been widely observed in cold-adapted proteases.